Meningkatkan Keterampilan Berbicara Bahasa Inggris Mahasiswa Program Studi Administrasi Rumah Sakit angkatan 17 Dengan Menggunakan Teknik Wawancara terhadap Turis: Improving the English Speaking Skill of the 17th Hospital Administration Students Using Three Steps Interview to Foreigners - Karmilah Karmilah (JURNAL TERAS KESEHATAN, 2019)
Referring to the Vision of Politeknik Al Islam Bandung , which is to become a leading higher education institution in the field of health that is appropriate, islamic, national standard and internationally oriented "and that vision has not been achieved because the English speaking skill is still lacking. Therefore, The objective of this research was to investigate the process of Three-Step interveiew technique to foreign tourists in teaching and learning, so that it can improve students' speaking skills in English. The research approach was qualitative, and the method used was Class Action Research. Technique collecting data was obtained through observation, documentation, test, and interview.The subjects of the study were 15 students of 17th Hospital Administration Study Program .The results of this research showd that the Three-Step Interview technique to foreigners can improve Students English speaking skills. That was proven by an increase from pre-test score 67.3 to post test 80, There was an increase of 12.7. Positive responses from students to the Three-Step Interview technique to foreign because it can add a pleasant learning experience and increase student confidence and ability to speak English